A porous thermal insulation material, a method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202410504961.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-04-24
AI Technical Summary
Existing lithium battery heat shields have complex structures and are quite thick, which affects the lightweighting of battery packs. Furthermore, the gases generated before the battery thermal runaway cannot be effectively removed, leading to an increased risk of battery pack decomposition and explosion.
A method for preparing porous thermal insulation materials is adopted, which involves impregnating fiber felt in a silicon-aluminum binary sol and modifying it with amino groups to form an amino-modified fiber felt. After drying, a porous thermal insulation material is obtained. The fiber felt is used as a carrier, and the amino-modified silicon-aluminum binary nanoporous material fills the gaps between the fibers to improve the gas adsorption efficiency.
It achieves efficient adsorption of gases generated during battery thermal runaway, blocks the propagation of thermal runaway, maintains battery energy density, and features high porosity, high temperature resistance, good thermal insulation performance, and elasticity and lightweight. Moreover, the production process is environmentally friendly and pollution-free.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of heat insulation and fireproof materials, and in particular to a porous heat insulation material, its preparation method and its application. Background Technology
[0002] A power battery is a rechargeable battery that directly or indirectly powers an electric vehicle. Power battery packs typically consist of hundreds or thousands of individual cells connected in series and parallel to form a battery module. If a single cell experiences thermal runaway, the enormous heat can be transferred to adjacent cells, causing the runaway to spread. To ensure the safety of power batteries, heat-insulating and fire-resistant materials are usually installed between the battery cells to prevent a thermally runaway cell or battery pack from igniting adjacent cells and to block the spread of thermal runaway from the runaway cell to the surrounding area. This reduces damage to the battery pack and its collateral damage. Fire-resistant and heat-insulating designs for the battery pack also provide occupants with more escape time and slow the spread of fire.
[0003] The application scenarios of new energy vehicles have placed new demands on flame-retardant and heat-insulating materials, such as thinness, high strength, vibration reduction, temperature resistance, low thermal conductivity, non-toxic gas production, waterproofing, moisture resistance, shock resistance, and insulation. Chinese patent application CN116154360A discloses a battery heat-insulating pad that exhibits excellent insulation performance under high-temperature conditions (above 500℃) and can maintain its heat-insulating performance at high temperatures, while also possessing mechanical strength and impact resistance. Chinese patent CN210326053U discloses a buffer heat-insulating pad for lithium-ion batteries, comprising upper and lower polymer film layers with a flame-retardant heat-insulating layer between them. However, existing lithium battery heat-insulating sheets have complex structures and are relatively thick, which affects the lightweighting of battery packs and leads to a decrease in their energy density. Furthermore, before a single battery cell is triggered to thermal runaway, the battery will generate gas when heated. The gas pressurizes the battery and can further accelerate the decomposition of the battery components, which can lead to continuous overheating of the battery and the generation of gas in the battery. If the battery temperature reaches the battery's critical temperature, the battery may catch fire or explode.
[0004] Therefore, there is an urgent need to provide a multifunctional heat insulation sheet and its production method that can effectively remove the gas generated in the limited space of the battery module and meet the high energy density requirements of new energy vehicle battery modules. Summary of the Invention
[0005] The technical problem solved by this invention is to provide a porous thermal insulation material that can effectively adsorb the gas generated by the battery when heated and block the spread of thermal runaway of the battery.
[0006] This application provides a method for preparing a porous thermal insulation material, including the following steps:
[0007] S1) Mix the silica-alumina binary sol and the coagulant to obtain the sol;
[0008] S2) The fiber felt is impregnated in the sol, and after gelation, it is modified with amino groups to obtain the modified fiber felt;
[0009] S3) The modified fiber felt is dried to obtain a porous thermal insulation material.
[0010] Preferably, step S2) specifically includes:
[0011] The fiber felt is impregnated in the sol, and after gelation, a wet gel / fiber felt composite is obtained.
[0012] The wet gel / fiber felt composite was modified by immersing it in a mixed solution of aminopropylmethyldiethoxysilane and organic alcohol to obtain the modified fiber felt.
[0013] Preferably, the organic alcohol includes methanol, ethanol or propanol, the volume ratio of aminopropylmethyldiethoxysilane to the organic alcohol is 1:(2~4), and the modification time is 1~5h.
[0014] Preferably, the preparation of the silica-alumina binary sol includes the following steps:
[0015] S11) A silicon precursor, an organic alcohol, water and a catalyst are mixed and hydrolyzed to obtain a silica sol;
[0016] An aluminum sol is obtained by mixing an aluminum precursor, an organic alcohol, and water and then hydrolyzing the mixture.
[0017] S12) The silica sol and the aluminum sol are mixed to obtain a silica-alumina binary sol.
[0018] Preferably, in the step of obtaining silica sol, the silicon precursor includes siloxane, the organic alcohol includes one or more of ethanol, methanol, isopropanol, n-butanol, sec-butanol, tert-butanol, and tert-amyl alcohol, the catalyst includes hydrochloric acid or sulfuric acid, the volume ratio of the silicon precursor, the organic alcohol, and the water is (9~15):(30~50):(1~10); the hydrolysis temperature is 40~60℃, and the time is 2~4h.
[0019] Preferably, in the step of obtaining aluminum sol, the aluminum precursor includes inorganic aluminum, and the organic alcohol includes one or more of ethanol, methanol, isopropanol, n-butanol, sec-butanol, tert-butanol, and tert-amyl alcohol; the hydrolysis temperature is 50~70℃, and the time is 2~4h.
[0020] Preferably, the coagulant includes ammonia or propylene oxide, the volume ratio of the coagulant to the siloxane is (1.5~8):1, and the mixing time of the coagulant and the silica-alumina binary sol is 10~60s.
[0021] Preferably, the fiber felt includes one of aluminum silicate felt, mullite fiber, glass fiber, pre-oxidized fiber felt and ceramic fiber, with a fiber diameter of 2~10μm and an aspect ratio of 100~150.
[0022] This application also provides a porous thermal insulation material prepared by the aforementioned preparation method, comprising fiber felt and an amino-modified silicon-aluminum porous material filling the gaps between the fiber felt.
[0023] This application also provides a battery module, including multiple individual cells and a porous heat insulation material disposed between adjacent individual cells, wherein the porous heat insulation material is the porous heat insulation material prepared by the preparation method described above or the porous heat insulation material described above.
[0024] This application provides a method for preparing a porous thermal insulation material. First, a silica-alumina sol is prepared. Then, a fiber felt is impregnated in the silica-alumina sol. After gelation, it is modified with amino groups to obtain an amino-modified fiber felt. After drying, a porous thermal insulation material is obtained. This material is a composite material in which the fiber felt serves as a carrier and support, and the amino-modified silica-alumina binary nanoporous material fills the gaps between the fibers. The amino-modified silica-alumina binary nanoporous material with uniform pore size distribution in the porous thermal insulation material prepared in this application increases the active sites for contact with gases generated by the battery, greatly improving the CO2 adsorption efficiency generated by the heated battery within the battery module. The silica-alumina binary nanoporous material enables the thermal insulation material to withstand an environment of 1000 ℃, and after 2 hours of heat treatment, the volume shrinkage rate is only 6.6%. Furthermore, the elasticity of the silica-alumina binary nanoporous material itself endows the thermal insulation material with mechanical strength and fatigue resistance, enabling it to adapt to the expansion and contraction of the battery during charging and discharging, as well as the huge impact generated during battery explosion.
[0025] Therefore, the porous thermal insulation material prepared in this application has the characteristics of high porosity, high temperature resistance, good thermal insulation performance and elasticity and light weight. It can achieve physical adsorption of gases generated during the thermal runaway process of the battery, and has the advantages of good low-concentration adsorption effect, strong adsorption binding energy and no risk of secondary pollution from desorption.
[0026] In addition, the porous thermal insulation material prepared in this application does not involve aging or solvent replacement during the preparation process, thus avoiding the use of a large amount of organic solvents. The drying process is short, the finished product has stable performance, and it can be produced continuously. Attached Figure Description
[0027] Figure 1 A photograph of the high-temperature resistant porous heat insulation sheet with gas adsorption function prepared in Example 1 of the present invention;
[0028] Figure 2 This is a scanning electron microscope image of the high-temperature resistant porous heat insulation sheet with gas adsorption function prepared in Example 1 of the present invention;
[0029] Figure 3 The nitrogen adsorption-desorption curve and pore size distribution diagram are shown for the high-temperature resistant porous heat insulation sheet with gas adsorption function prepared in Example 1 of the present invention.
[0030] Figure 4 The stress-strain curve of the high-temperature resistant porous heat insulation sheet with gas adsorption function prepared in Example 1 of the present invention is shown.
[0031] Figure 5 The volume shrinkage rate of the high-temperature resistant porous heat insulation sheet with gas adsorption function prepared in Example 1 of the present invention after heat treatment at different temperatures is shown in the figure.
[0032] Figure 6 Comparison of CO2 concentration generated in a battery when high-temperature resistant porous heat insulation sheets with gas adsorption function prepared in Example 2 of the present invention are applied to a battery thermal runaway propagation experiment.
[0033] Figure 7 The nitrogen adsorption-desorption curve and pore size distribution diagram of the porous heat insulation sheet prepared in Comparative Example 1 of this invention are shown.
[0034] Figure 8 This is based on the principle of amino surface modification reaction. Detailed Implementation
[0035] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims of the present invention.
[0036] To effectively remove gases generated by battery modules and block the propagation of thermal failure, this application provides a method for preparing a porous thermal insulation material, comprising a fiber felt and an amino-modified silicon-aluminum binary nanoporous material filling the gaps between the fiber felt. The silicon-aluminum binary nanoporous material can physically adsorb gases generated during battery thermal runaway and possesses high-temperature resistance and good thermal insulation performance. The fiber felt is elastic and lightweight. Therefore, the porous thermal insulation material provided by this application can effectively remove gases generated by battery modules and achieve a blocking effect. Specifically, this invention discloses a method for preparing a porous thermal insulation material, including the following steps:
[0037] S1) Mix the silica-alumina binary sol and the coagulant to obtain the sol;
[0038] S2) The fiber felt is impregnated in the sol, and after gelation, it is modified with amino groups to obtain the modified fiber felt;
[0039] S3) The modified fiber felt is dried to obtain a porous thermal insulation material.
[0040] In the preparation of porous thermal insulation materials, as a preferred embodiment, this application first prepares silica sol and aluminum sol. The preparation of the silica sol specifically involves mixing a silicon precursor, an organic alcohol, water, and a catalyst, followed by hydrolysis to obtain the silica sol. The silicon precursor can be a siloxane, more specifically, tetraethyl orthosilicate. The organic alcohol is an organic alcohol well-known to those skilled in the art; for example, it includes one or more of ethanol, methanol, isopropanol, n-butanol, sec-butanol, tert-butanol, and tert-amyl alcohol. The catalyst is used to promote the hydrolysis of the silicon precursor and is specifically selected from hydrochloric acid or sulfuric acid. The volume ratio of the silicon precursor, the organic alcohol, and the water is (9~15):(30~50):(1~10), specifically, the volume ratio is (10~13):(35~45):(2~8). To ensure complete hydrolysis of the silicon precursor, the silicon precursor, organic alcohol, water, and catalyst are mixed and stirred until homogeneous, then heated in a water bath to obtain a silica sol. Specifically, magnetic stirring can be used, and the stirring time is 2-4 hours. The hydrolysis temperature is 40-60°C, specifically, the stirring time is 2 hours, 2.5 hours, 3 hours, 3.5 hours, or 4 hours, and the hydrolysis temperature is 40°C, 43°C, 45°C, 48°C, 50°C, 52°C, 55°C, 58°C, or 60°C. The aluminum sol is prepared by mixing an aluminum precursor, organic alcohol, and water, and then hydrolyzing to obtain an aluminum sol. The aluminum precursor can be inorganic aluminum, more specifically, aluminum chloride hexahydrate. The organic alcohol is a well-known organic alcohol, for example, including one or more of ethanol, methanol, isopropanol, n-butanol, sec-butanol, tert-butanol, and tert-amyl alcohol. To ensure complete hydrolysis of the aluminum precursor, the aluminum precursor, organic alcohol, and water are mixed and stirred until homogeneous, then heated in a water bath to obtain an aluminum sol. Specifically, magnetic stirring can be used, and the stirring time is 2-4 hours. The hydrolysis temperature is 50-70°C. Specifically, the stirring time is 2 hours, 2.5 hours, 3 hours, 3.5 hours, or 4 hours, and the hydrolysis temperature is 50°C, 53°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, or 70°C.
[0041] This application then mixes the silica sol and the aluminum sol to obtain a silica-alumina binary sol; the volume ratio of the silica sol to the aluminum sol is (3~5):1.
[0042] After obtaining the silica-alumina binary sol, it is mixed with a coagulant to obtain a sol. The mixing time is 10-60 s, specifically 10 s, 12 s, 16 s, 20 s, 24 s, 28 s, 32 s, 35 s, 40 s, 42 s, 45 s, 48 s, 50 s, 52 s, 55 s, 58 s, or 60 s. The coagulant promotes the polymerization of silanol groups in the silica-alumina binary sol, but the above mixing does not achieve the transformation of the sol into a gel; it remains a sol. The coagulant includes ammonia or propylene oxide, and the volume ratio of the coagulant to the siloxane is (1.5-8):1, specifically (1.7-6):1, and more specifically (2-5):1.
[0043] This application then impregnates the fiber felt in the above sol, and after gelation, performs amino modification to obtain modified fiber felt. Specifically, the fiber felt is impregnated in the sol, ensuring the sol fully fills the pores and surface of the fiber felt. After complete gelation, the surface of the obtained wet gel / fiber felt composite is modified using a mixed solution of aminopropylmethyldiethoxysilane and organic alcohol. The specific reaction process for amino modification is as follows: Figure 8 As shown; if aminopropylmethyldiethoxysilane is added before gelation, it will affect the gelation process, resulting in flocculent matter and extremely low gel skeleton strength. The fiber felt is a fiber felt well known to those skilled in the art. For example, the fiber felt includes one of aluminum silicate felt, mullite fiber, glass fiber, pre-oxidized fiber felt, and ceramic fiber, with a fiber diameter of 2~10μm and an aspect ratio of 100~150. The porosity of the fiber felt determines the mass fraction of aerogel in the high-temperature porous insulation sheet. If the fiber felt is relatively dense, there are fewer pores, the strength is greater, and it can support less aerogel. If the fiber felt is relatively loose, more aerogel can fill the fiber felt, and the insulation effect may be better. Therefore, as a substrate for porous thermal insulation materials, aerogel itself lacks sufficient mechanical strength to withstand the long-term vibration environment of electric vehicles. Thus, a reinforcing phase, namely fiber felt, is required. Fiber felt is made of micron-sized fibers overlapping together, with controllable thickness and mature production technology. There are micron to millimeter-sized pores between the fibers. When aerogel fills the pores of the fiber felt, the aerogel-fiber felt composite material has both strong compressive strength and excellent thermal insulation performance. Therefore, fiber felt as a reinforcing material greatly expands the application field of aerogel.
[0044] The organic alcohol, used as an interface agent, includes methanol, ethanol, or propanol. The volume ratio of aminopropylmethyldiethoxysilane to the organic alcohol is 1:2 to 4, specifically, the volume ratio of aminopropylmethyldiethoxysilane to the organic alcohol is 1:2. The modification time is 1 to 5 hours, specifically, the modification time is 2 to 4 hours.
[0045] Finally, the modified fiber felt is dried to obtain a porous thermal insulation material. The drying process can be carried out in a supercritical drying apparatus at a temperature of 30–280°C for 1–5 hours; specifically, at a temperature of 50–250°C for 2–4 hours; more specifically, at a temperature of 80–200°C for 3 hours. Gradient drying can also be used, i.e., drying at a gradient of 60°C, 80°C, and 100°C. This gradient drying method allows for more thorough removal of impurities and slows down the drying rate, which helps protect the three-dimensional network structure and prevents collapse. The porous thermal insulation material prepared according to the above method is a porous thermal insulation sheet.
[0046] This application also provides a porous thermal insulation material, comprising a fiber felt and an amino-modified aluminum silicate porous material filling the gaps between the fiber felt, namely, a fiber felt and an amino-modified aluminum silicate aerogel filling the gaps between the fiber felt. The porous thermal insulation material provided in this application has a specific surface area of 390~500 m². 2 / g, wherein the silicon-aluminum porous material has a nanoporous structure with a relatively concentrated pore size distribution (20~50nm) and uniform size, and the fiber diameter of the fiber felt ranges from 2 to 10μm with an aspect ratio of 100~150. In this application, the amino-modified silicon-aluminum porous material accounts for 20~60wt% of the porous thermal insulation material, specifically, the amino-modified silicon-aluminum porous material accounts for 25~55wt% of the porous thermal insulation material, and more specifically, the amino-modified silicon-aluminum porous material accounts for 30~50wt% of the porous thermal insulation material.
[0047] This application also provides a battery module, which includes multiple individual cells and a porous heat insulation material disposed between adjacent individual cells, wherein the porous heat insulation material is the porous heat insulation material described in the above-mentioned solution.
[0048] The amino-modified silicon-aluminum binary porous material in the porous thermal insulation material provided by this invention is an adsorbent material. This porous material has an excellent nano-network structure, which accelerates the diffusion and mass transfer capacity and adsorption rate between the gas and the porous material. In addition to the gas adsorption function, this porous thermal insulation material can also effectively block the propagation of thermal runaway, ensuring battery safety without significantly affecting the battery energy density. Moreover, the production process is simple and environmentally friendly, making it a multifunctional battery safety material.
[0049] To further understand the present invention, the preparation method of the porous thermal insulation material provided by the present invention will be described in detail below with reference to the embodiments. The scope of protection of the present invention is not limited by the following embodiments.
[0050] Example 1
[0051] The volume ratio of tetraethyl orthosilicate:ethanol:deionized water:catalyst (dilute hydrochloric acid) was 11.5:40:2:2. 34.5 ml of tetraethyl orthosilicate, 120 ml of ethanol, and 6 ml of deionized water were mixed, followed by the addition of 6 ml of dilute hydrochloric acid. The mixture was stirred continuously on a magnetic stirrer for 2 hours while simultaneously heating in a water bath at 45 °C to ensure complete hydrolysis of the tetraethyl orthosilicate. Alternatively, the volume ratio of ethanol:deionized water was 58.2:25.2. 58.2 ml of ethanol and 25.2 ml of deionized water were mixed, followed by the addition of 24.2 g of aluminum chloride hexahydrate. The mixture was stirred continuously on a magnetic stirrer for 70 minutes while simultaneously heating in a water bath at 50 °C to ensure complete hydrolysis of the aluminum chloride hexahydrate. After 2 hours, the mixture was stirred at room temperature for 8 hours, followed by the addition of 60 ml of propylene oxide. Stirring was stopped after 10 seconds.
[0052] Next, the aluminosilicate fiber felt was immersed in the above sol solution. After complete immersion and gelation, it was removed and the wet gel / fiber felt composite was modified by immersing it in a mixed solution of aminopropylmethyldiethoxysilane and ethanol (volume ratio of aminopropylmethyldiethoxysilane to ethanol: 1:2) for 2 hours. The modified composite was then placed in a supercritical drying apparatus for supercritical drying to obtain a high-temperature resistant porous heat insulation sheet with gas adsorption function. The specific surface area of this porous heat insulation sheet is 465 m². 2 / g.
[0053] Figure 1 This is a photograph of the high-temperature resistant porous heat insulation sheet prepared in this embodiment. Figure 2 Scanning electron microscope (SEM) images of high-temperature resistant porous thermal insulation sheets, produced by... Figure 2 It is known that the pores of the fiber felt are filled with a large number of aerogel blocks. These aerogel blocks are attached to the fiber surface. Further magnification of the aerogel reveals that it is composed of countless secondary particles spliced together, with uniform three-dimensional nanopores between the particles. This structure results in the excellent thermal insulation performance of the aerogel.
[0054] Figure 3 The nitrogen adsorption-desorption curves and pore size distribution diagrams of the high-temperature resistant porous heat insulation sheet prepared in this embodiment are obtained from... Figure 3It is known that the pore size distribution of the thermal insulation sheet is mostly between 10 and 60 nm, proving that it contains abundant mesopores. The pore size of mesoporous thermal insulation materials is smaller than the free path of gas molecule collisions (70 nm), preventing gas molecules involved in heat transfer from passing through, thus essentially cutting off the heat conduction of gas molecules. Due to the existence of nearly infinite mesopores, heat flow in the solid can only be transferred along the pore walls. The nearly infinite number of pore walls constitutes a near "infinitely long path" effect, greatly reducing the thermal conductivity of the solid. In addition, air molecules therefore lose their ability to flow freely and cannot participate in thermal convection. The nitrogen adsorption-desorption isotherm belongs to Type IV in the IUPAC classification, H1 hysteresis loop. The characteristics of the hysteresis loop correspond to specific pore structure information, and H1 is a uniform pore model.
[0055] Figure 4 The stress-strain curve of the high-temperature resistant porous heat insulation sheet prepared in this embodiment is shown in the figure. Figure 4 It can be seen that under 40% deformation, the compression cycle test curves of 1000 cycles basically overlap, proving that the high-temperature resistant porous heat insulation sheet has good resilience performance and can withstand a maximum pressure of at least 600 kPa.
[0056] Figure 5 The volumetric linear shrinkage rate of the high-temperature resistant porous heat insulation sheet prepared in this embodiment after heat treatment at different temperatures is given by... Figure 5 It can be seen that after being treated at 1150℃ for 2 hours, the linear shrinkage rate of the high-temperature resistant porous heat insulation sheet is 10%, and the volume shrinkage rate only increases significantly after being treated at 1200℃, proving that the heat resistance temperature of the high-temperature resistant porous heat insulation sheet is around 1100℃.
[0057] Example 2
[0058] The volume ratio of tetraethyl orthosilicate:ethanol:deionized water:catalyst (dilute hydrochloric acid) was 11.5:40:6:1. 34.5 ml of tetraethyl orthosilicate, 120 ml of ethanol, and 18 ml of deionized water were mixed, followed by the addition of 3 ml of dilute hydrochloric acid. The mixture was stirred continuously on a magnetic stirrer for 2 hours while simultaneously heating in a water bath at 45 °C to ensure complete hydrolysis of the tetraethyl orthosilicate. Alternatively, the volume ratio of ethanol:deionized water was 58.2:25.2. 58.2 ml of ethanol and 25.2 ml of deionized water were mixed, followed by the addition of 24.2 g of aluminum chloride hexahydrate. The mixture was stirred continuously on a magnetic stirrer for 70 minutes while simultaneously heating in a water bath at 50 °C to ensure complete hydrolysis of the aluminum chloride hexahydrate. After 2 hours, the mixture was stirred at room temperature for another 2 hours, followed by the addition of 60 ml of propylene oxide. Stirring was stopped after 10 seconds.
[0059] Next, the aluminosilicate fiber felt was immersed in the above sol solution. After complete immersion and gelation, it was removed and the wet gel / fiber felt composite was modified by immersing it in a mixed solution of aminopropylmethyldiethoxysilane and ethanol (volume ratio of aminopropylmethyldiethoxysilane to ethanol: 1:2) for 2 hours. The modified composite was then placed in a supercritical drying apparatus for supercritical drying to obtain a high-temperature resistant porous heat insulation sheet with gas adsorption function. The specific surface area of this porous heat insulation sheet is 421 m². 2 / g.
[0060] The battery thermal runaway propagation experiment specifically involved: placing a high-temperature resistant porous insulation sheet between batteries, observing the opening of the battery safety valve, and the concentration and amount of CO2 generated during thermal runaway. Figure 6 As shown, Figure 6 This example compares the CO2 concentration generated in a battery during a thermal runaway propagation experiment using porous thermal insulation sheets with different contents of silicon-aluminum porous material (23.1%, 35.7%, 44.5%, 51.1%) and a blank control thermal insulation sheet. Figure 6 It can be seen that the CO2 generated when the battery safety valve opens and during thermal runaway is absorbed by the porous heat insulation sheet, thus significantly reducing the amount of CO2 released into the environment (detected by the gas detector). These correspond to the CO2 detection amounts in groups 3 to 6, with group 1 corresponding to the CO2 detection amount without the addition of the high-temperature resistant porous heat insulation sheet, and group 2 corresponding to the CO2 detection amount of pure fiber felt (without aerogel).
[0061] Example 3
[0062] The raw material tetraethyl orthosilicate:ethanol:deionized water:catalyst (dilute hydrochloric acid) volume ratio was 11.5:40:2:2. 34.5 ml of tetraethyl orthosilicate, 120 ml of ethanol, and 6 ml of deionized water were mixed, followed by the addition of 6 ml of dilute hydrochloric acid. The mixture was stirred continuously on a magnetic stirrer for 2 h, while simultaneously heating in a water bath at 45 ℃ to ensure complete hydrolysis of the tetraethyl orthosilicate. Alternatively, the raw material volume ratio of ethanol:deionized water was 4:1. 60 ml of ethanol and 15 ml of deionized water were mixed, followed by the addition of 24.2 g of aluminum chloride hexahydrate. The mixture was stirred continuously on a magnetic stirrer for 70 min, while simultaneously heating in a water bath at 50 ℃ to ensure complete hydrolysis of the aluminum chloride hexahydrate. After 2 h, the mixture was stirred at room temperature for 2 h, and then 60 ml of propylene oxide was added. Stirring was stopped after 10 s.
[0063] Next, the aluminosilicate fiber felt was immersed in the above sol solution. After complete immersion and gelation, it was removed and the wet gel / fiber felt composite was modified by immersing it in a mixed solution of aminopropylmethyldiethoxysilane and ethanol (volume ratio of aminopropylmethyldiethoxysilane to ethanol: 1:2) for 2 hours. The modified composite was then subjected to a gradient drying program at 60 °C, 80 °C, and 100 °C for atmospheric pressure drying, thus obtaining a high-temperature resistant porous heat insulation sheet with gas adsorption function. The specific surface area of this porous heat insulation sheet is 394 m². 2 / g.
[0064] Comparative Example 1
[0065] The volume ratio of tetraethyl orthosilicate: ethanol: deionized water: catalyst (dilute hydrochloric acid) is 11.5: 40: 2: 2. Mix 34.5 ml of tetraethyl orthosilicate with 120 ml of ethanol and 6 ml of deionized water, then add 6 ml of dilute hydrochloric acid and heat in a water bath at 45 ℃ to fully hydrolyze the tetraethyl orthosilicate. Stir continuously on a magnetic stirrer for 2 h, then add 6 ml of dilute ammonia water and stop stirring after 1 min.
[0066] Next, the aluminosilicate fiber felt is immersed in the above sol solution. After complete immersion, it is removed and placed at room temperature to allow gelation. Then, it is placed in an oven at 60 °C for normal pressure drying to obtain a high-temperature resistant porous heat insulation sheet with gas adsorption function. The specific surface area of this porous material heat insulation sheet is 261 m². 2 / g. The nitrogen adsorption-desorption curves and pore size distribution diagram of this porous thermal insulation material are shown below. Figure 7 As shown.
[0067] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.
[0068] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a porous thermal insulation material, comprising the following steps: S1) Mix the silica-alumina binary sol and the coagulant to obtain the sol; S2) The fiber felt is impregnated in the sol, and after gelation, it is modified with amino groups to obtain the modified fiber felt; the modification time is 1~5h. S3) The modified fiber felt is dried to obtain a porous thermal insulation material; Step S2) specifically refers to: The fiber felt is impregnated in the sol, and after gelation, a wet gel / fiber felt composite is obtained. The wet gel / fiber felt composite was modified by soaking it in a mixed solution of aminopropylmethyldiethoxysilane and organic alcohol to obtain modified fiber felt; the volume ratio of aminopropylmethyldiethoxysilane to organic alcohol was 1:(2~4). The fiber diameter of the fiber felt is 2~10μm and the aspect ratio is 100~150; The porous thermal insulation material has a pore size distribution of 10~60nm; The porous thermal insulation material includes fiber felt and amino-modified silicon-aluminum porous material filling the gaps between the fiber felt.
2. The preparation method according to claim 1, characterized in that, The organic alcohols include methanol, ethanol, or propanol.
3. The preparation method according to claim 1, characterized in that, The preparation of the silica-alumina binary sol includes the following steps: S11) A silicon precursor, an organic alcohol, water and a catalyst are mixed and hydrolyzed to obtain a silica sol; An aluminum sol is obtained by mixing an aluminum precursor, an organic alcohol, and water and then hydrolyzing the mixture. S12) The silica sol and the aluminum sol are mixed to obtain a silica-alumina binary sol.
4. The preparation method according to claim 3, characterized in that, In the step of obtaining silica sol, the silicon precursor includes siloxane, the organic alcohol includes one or more of ethanol, methanol, isopropanol, n-butanol, sec-butanol, tert-butanol, and tert-amyl alcohol, the catalyst includes hydrochloric acid or sulfuric acid, and the volume ratio of the silicon precursor, the organic alcohol, and the water is (9~15):(30~50):(1~10); the hydrolysis temperature is 40~60℃, and the time is 2~4h.
5. The preparation method according to claim 3, characterized in that, In the step of obtaining aluminum sol, the aluminum precursor includes inorganic aluminum, and the organic alcohol includes one or more of ethanol, methanol, isopropanol, n-butanol, sec-butanol, tert-butanol, and tert-amyl alcohol; the hydrolysis temperature is 50~70℃, and the time is 2~4h.
6. The preparation method according to claim 4, characterized in that, The coagulant includes ammonia or propylene oxide, the volume ratio of the coagulant to the siloxane is (1.5~8):1, and the mixing time of the coagulant and the silica-alumina binary sol is 10~60s.
7. The preparation method according to claim 4, characterized in that, Fiber felts include one of the following: aluminosilicate felt, mullite fiber, glass fiber, pre-oxidized fiber felt, and ceramic fiber.
8. The porous thermal insulation material prepared by the preparation method according to any one of claims 1 to 7 comprises fiber felt and amino-modified silicon-aluminum porous material filling the gaps between the fiber felt.
9. A battery module comprising a plurality of individual cells and a porous heat-insulating material disposed between adjacent individual cells, wherein the porous heat-insulating material is a porous heat-insulating material prepared by the preparation method according to any one of claims 1 to 7 or a porous heat-insulating material according to claim 8.
Citation Information
Patent Citations
Battery thermal insulation spacer
CN116154360A
Novel buffer heat insulation pad for lithium ion battery
CN210326053U
Amino-modified silica aerogel and application thereof to heavy metal ion adsorbent
CN103432985A
Preparation method of silicon-aluminum binary aerogel composite material
CN114100534A
